English Language Prose Written By Pandit Jawaharlal Nehru As a Writer: Exploring Nehru's Metaphorical Language and Historical Reflections (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Nehru Had A NaturallyMetaphorical Cast Of Mind. He Is Often Found On These Pages Comparing HistoryTo A Great River. Indeed, He Thought A Lot About History, And Felt Keenly ThePressure Of History. In A Speech To The Contituent Assembly In 1947, HeImagines Himself "Standing On The Sword's Edge Of The Present Between TheMighty Past And The Mightier Future" - A Particularly Good Metaphor,Because It Suggests How Fraught With Uncertainty The Present Is, Possessing ThePower To Cut Sharply Even As Attempts Are Made To Work With It. Elsewhere, HeLikens The Taking Of Risks To The Exhilaration Of Climbing The Mountains, WhileThose Who Hold Back, Desiring Safety And Security, Are Seen As Living In TheValley, "With Their Unhealthy Mists And Fogs". This Metaphor ShowsAmong Other Things Nehru's Love Of Mountains, For Most Indians Would Hardly GoAlong With His Negative Characterization Of Valleys.